Em busca de alternativas energéticas: estudo sobre as pesquisas em células combustíveis no Brasil - Lorenzi, Bruno Rossi (Universidade Federal de São Carlos, 2012)
This dissertation has aims to make an analysis of the political and sociological dimensions on the research in fuel cells and hydrogen energetic use in Brazil. For this we have done an extensive bibliographic research about this theme and other related (as energy policy and environment) and a case study about the CENEH (Centro Nacional de Referência em Energia do Hidrogênio), a public center of research and consultation in technologies related to the hydrogen and fuel cells. As a theoretical background, we start from the sociology of science, specially the Actor-Network Theory by Bruno Latour and Michel Callon. Through this research, we found many social actors related to this area, their actions, relations and tensions, and also a view of the technological and political situation of the research and development of the hydrogen energetic use at the networks articulated by the CENEH.
In search of energy alternatives: a study on fuel cells research in Brazil
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Células a combustível; Hidrogênio; Centro Nacional de Referência em Energia do Hidrogênio; Ciência - aspectos sociais; Fuel cells; Hydrogen; CENEH; Sociology of Science; CIENCIAS SOCIAIS APLICADAS